Multipurpose plants in the Northern Libya rangeland area of Syrt - Pardini A.; Battaglia M.; Giunta R. (Ecosystem services and socio-economic benefits of Mediterranean grasslands, 2016)
Urbanization and irrigation plans strongly implemented by the passed Gheddafi’s government started the abandonment of rangeland in the northern part of Libya. Sedentarization also caused the loss of nomad traditions, including knowledge of wild forages, food and medicinal plants that could become new industries in the future after selection and analytical scientific investigation. A trial was carried out in 2009 in the Syrt rangeland just before the start of the war, in order to identify existing wild multipurpose plants and their traditional uses. The trial was managed thanks to agreements of The Italian Agronomic Institute for Overseas (Foreign Ministry), the University of Florence, and the University of Syrt (now destroyed). The results have shown the existence of a wide plant diversity and a good balance of the plants\' specific contributions. The most common plants include wild grasses and legumes and few shrubs of the steppe vegetation. In spite of the traditions being lost, herders still know traditional uses of many plants, uses that have not been yet scientifically investigated. Further research would be needed as soon as new security conditions in the area will make them possible again.
15. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM International Network for the Research and Development of Pastures and Fodder Crops, 2016/04/12-14, Orestiada (Greece)